Probing Versus Intubation in Simple and Complex Congenital Nasolacrimal Duct Obstruction: A Systematic Review and Meta-Analysis - Faheemullah Behsoodwal; Qareebullah Ameer (Jurnal Health Sains, 2026)
Congenital Nasolacrimal Duct Obstruction (CNLDO) is one of the most common lacrimal disorders in children, affecting 6–20% of neonates and occurring at an incidence of 23.1 per 10,000 live births. This systematic review and meta-analysis compared the effectiveness of nasolacrimal duct probing and intubation in simple and complex CNLDO, evaluated the moderating effect of patient age on treatment outcomes, and synthesised complication profiles associated with both interventions. A systematic search of PubMed, EMBASE, Cochrane Library, and Web of Science identified relevant studies published between January 2002 and March 2026. Following PRISMA-compliant screening procedures, 21 studies involving 2,593 patients met the inclusion criteria, with excellent inter-rater agreement (kappa = 0.89). In simple CNLDO, treatment success did not differ significantly between probing and intubation (RR = 0.94; 95% CI: 0.88–1.01; I² = 38%), supporting probing as an appropriate first-line intervention. Conversely, intubation demonstrated significantly superior outcomes in complex CNLDO (RR = 0.57 favouring intubation; 95% CI: 0.49–0.66; I² = 52%). The pooled success rates for intubation and probing in complex cases were 82.4% and 45.8%, respectively. Age significantly moderated treatment effectiveness, with children older than 24 months experiencing markedly poorer outcomes following probing in complex CNLDO (interaction p = 0.003). These findings support subtype-based treatment strategies, recommending probing for simple CNLDO and early intubation for complex cases. Further high-quality randomised trials are required to strengthen the evidence base and standardise complexity definitions.